Does the time inconsistency problem make flexible exchange rates look worse than you think? - Roc Armenter; Martin Bodenstein (Federal Reserve Bank of New York, 2005)
Lack of commitment in monetary policy leads to the well known Barro-Gordon inflation bias. In this paper, we argue that two phenomena associated with the time inconsistency problem have been overlooked in the exchange rate debate. We show that, absent commitment, independent monetary policy can also induce expectation traps - that is, welfare-ranked multiple equilibria - and perverse policy responses to real shocks - that is, an equilibrium policy response that is welfare inferior to policy inaction. Both possibilities imply higher macroeconomic volatility under flexible exchange rates than under fixed exchange rates.
Keywords: E61; E33; F41; 330; time inconsistency; independent monetary policy; exchange rate regimes; Wechselkurssystem; Zeitkonsistenz; Geldpolitik; Theorie